2017
DOI: 10.1016/j.labeco.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Trends in earnings inequality and earnings instability among U.S. couples: How important is assortative matching?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 33 publications
1
26
1
1
Order By: Relevance
“…Despite concerns that changes in homogamy within couples might have contributed to increased income inequality (Breen and Salazar, 2011;Esping-Andersen, 2007;Schwartz, 2013;Western et al, 2008), most previous studies on the topic concluded that changes in educational homogamy have had little impact on income inequality (Breen and Salazar, 2010;2011;Breen and Andersen, 2012;Eika et al, 2014;Harmenberg, 2014;Hryshko et al, 2015). In this article, we extended this finding to a wide set of European countries.…”
Section: Discussionmentioning
confidence: 71%
“…Despite concerns that changes in homogamy within couples might have contributed to increased income inequality (Breen and Salazar, 2011;Esping-Andersen, 2007;Schwartz, 2013;Western et al, 2008), most previous studies on the topic concluded that changes in educational homogamy have had little impact on income inequality (Breen and Salazar, 2010;2011;Breen and Andersen, 2012;Eika et al, 2014;Harmenberg, 2014;Hryshko et al, 2015). In this article, we extended this finding to a wide set of European countries.…”
Section: Discussionmentioning
confidence: 71%
“…household heads, Black families, and families headed by a single-mother-reported the highest levels of earnings and income volatility and the largest increases in volatility over time (Gennetian, Rodrigues, Hill, & Morris, 2018a;Hardy, 2017;Hardy & Ziliak, 2014;Hryshko, Juhn, & McCue, 2017;Keys, 2008;Latner, 2018;Morduch & Schneider, 2016). Even married families are not necessarily protected from volatility because partners may work within the same sectors of the economy and suffer the same economic cycles (Ziliak et al, 2011).…”
Section: The Rise In Earnings and Income Volatilitymentioning
confidence: 99%
“…Hryshko et al . () examine the role of wives’ earnings for US household earnings inequality and stability; counterfactual earnings are constructed by randomly rematching married men and women, and using the combined earnings. They find that coordination of spouses’ labour supply decisions and positive assortative mating play a minor role.…”
Section: Background and Literaturementioning
confidence: 99%
“…; Hryshko et al . ), the procedure ignores the fact that the amount of earnings not only depends on earnings potential, but is also the result of an endogenous labour supply decision. This depends on the household context, in particular the spouse's characteristics.…”
Section: Introductionmentioning
confidence: 99%